2013
DOI: 10.1063/1.4820464
|View full text |Cite
|
Sign up to set email alerts
|

Renormalized bands and low-temperature colossal thermopower induced by Ir doping in Ca3Co4O9 system

Abstract: The effects of Ir doping on the low-temperature thermal and electrical transport properties of Ca3Co4−xIrxO9 (0 ≤ x ≤ 0.4) have been investigated. As Ir ions are doped into the system, a low-temperature thermopower upturn is introduced, and the temperature corresponding to the minimum thermopower TSmin increases monotonously with increasing x. Moreover, a low-temperature colossal thermopower is observed in the Ir-doped samples, which is beneficial to the low-temperature thermoelectric refrigeration in supercon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Using the classical relation R H ¼ 1/ne, these values correspond to a charge carrier concentration n of 5.7 Â 10 20 (0.047 per formula unit) and 3.9 Â 10 20 cm À3 (0.032 per formula unit), respectively. These values are in agreement with carrier concentrations for CCO derived from Hall effect measurements reported by others, [13][14][15][16][17][18][19][20][21]39 but in disagreement with estimates for the charge carrier concentration made from other techniques, as explained in the introduction. In general, the transport properties of CCO are highly anisotropic caused by its layered crystal structure, with relatively high conductivity within the COL (along the ab-direction) and low conductivity across (along c).…”
Section: Resultssupporting
confidence: 90%
“…Using the classical relation R H ¼ 1/ne, these values correspond to a charge carrier concentration n of 5.7 Â 10 20 (0.047 per formula unit) and 3.9 Â 10 20 cm À3 (0.032 per formula unit), respectively. These values are in agreement with carrier concentrations for CCO derived from Hall effect measurements reported by others, [13][14][15][16][17][18][19][20][21]39 but in disagreement with estimates for the charge carrier concentration made from other techniques, as explained in the introduction. In general, the transport properties of CCO are highly anisotropic caused by its layered crystal structure, with relatively high conductivity within the COL (along the ab-direction) and low conductivity across (along c).…”
Section: Resultssupporting
confidence: 90%
“…33 However, for our particular system, previous studies have shown that relative changes of p, such as the increase found by us, are qualitatively accurate, as long as data are compared at a constant temperature. [34][35][36][37] We find that the hole carrier density increases by about 20% in the presence of Co 3 O 4 . The larger charge density explains the drop in resistivity both qualitatively and quantitatively.…”
Section: Materials and Experimental Methodsmentioning
confidence: 67%
“…Turning to the Seebeck coefficients, it was found they could be significantly enhanced by substituting Fe 3+ , Mn 4+ or Ir 4+ for Co 3+ in the [CoO 2 ] layers [36,41,58]. Wang et al [36,41] examined the variation in effective mass (m * ) when 2.5 at.% Fe 3+ and Mn 4+ were substituted into calcium cobaltite, and fitted relevant specific heat capacity data using equation ( 5) [59]:…”
Section: Elemental Dopingmentioning
confidence: 99%
“…In particular, the power factor for the 2.5 at.% Fe 3+ substituted material (0.7 mWm −1 K −2 at 1000 K) is nearly triple that for undoped calcium cobaltite. Huang et al [58] proposed that Ir 4+ substitution for Co 3+ enhances the thermopower because Ir doping helps to extend the electronic band in the vicinity of the Fermi level; the band structure is renormalized by enhanced carrier localization. Consequently, the maximum valence band is decreased whilst the band gap is increased, leading to enhanced Seebeck coefficients according to equation ( 6) [65]:…”
Section: Elemental Dopingmentioning
confidence: 99%